Accuracy of two methods for measuring standing balance in children aged 7-12 years - Kunritt, Jaruta; Lekskulchai, Raweewan (Journal of Associated Medical Sciences, 2017)
Background: Balance is importance for motor development and sport participations. Standardized assessments of balance are required so that more children could have easily access to testing. Objectives: To test the accuracy of two standardized balance assessments including Pediatric Clinical Test of Sensory Interaction for Balance (P-CTSIB) and Balance Subtest of Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2) in Thai children. Materials and methods: Research participants included 44 children aged between 7 and 12 years. All children received balance assessments by two physical therapists blinded to the study protocol. The first physical therapist tested the children with appropriate testing for each child and the second physical therapists tested the children with one leg standing and heel to toe standing. Result of the two physical therapists were used to identify whether each child has or has no balance problem. Then the children were evaluated using the standard protocols of P-CTSIB and Balance Subtest of BOT-2. Primary outcome of this study were the validity indexes of P-CTSIB and Balance subtest of BOT-2. Results: P-CTSIB and Balance Subtest of BOT-2 showed the moderate to high levels of sensitivity (96%, 76%), specificity (89.50%, 63.20%) and accuracy (93.18%, 70.45%) when comparing to the clinical test of balance. Conclusion: The two selected standardized tests could be used to test balance of children when fully access to physical therapy clinic is not possible. These two standardized tests have benefit in different ways. The P-CTSIB should be selected, if the assessor needs to identify the sensory interaction to balance, while the BOT-2 tests functional balance.